Novel magnetron sputtered yttrium-silicon-iron oxide as CMAS resistant top coat material for environmental barrier coatings. (1st May 2023) - Rose, Alexandra; Gomez Chavez, Juan J.; Mechnich, Peter; Kelm, Klemens; Schulz, Uwe; Naraparaju, Ravisankar
Abstract: A nano-crystalline coating containing X2-yttrium monosilicate, yttrium ferrite and yttria was developed as a potential CaO-MgO-Al2 O3 -SiO2 (CMAS) resistant top layer for Environmental Barrier Coatings (EBCs) to protect Ceramic Matrix Composites. High temperature reactions at 1300 °C with a synthetic CMAS and Colima volcanic ash revealed that the phases react quickly with the melt to oxyapatite and garnet which effectively restricted the infiltration into the coating. The Fe played a major role in stabilizing the multi-phase coating as well as X2-yttrium monosilicate. Iron-free YSi-Ox coatings could not induce garnet formation and found to be less effective in restricting the CMAS infiltration. Graphical Abstract: ga1 Highlights: A novel multi-phase (X2-YMS, Y2O3 and YFeO3) coating was developed using magnetron sputtering methods. Uniform nano-crystalline coating microstructure has been achieved. Excellent CMAS resistance has been executed with two different (Ca-rich and Ca-lean) CMAS compositions. Offers a great potential as CMAS resistant top coat on state-of-the art EBC materials.